Gastropod pedal mucus retains microplastics and promotes the uptake of particles by marine periwinkles. (March 2019) - Gutow, Lars; Bartl, Kevin; Saborowski, Reinhard; Beermann, Jan
Abstract: The rapid dissemination of microplastics in many habitats of the oceans has raised concerns about the consequences for marine biota and ecosystems. Many adverse effects of microplastics on marine invertebrates are consequences of ingestion. Accordingly, the identification of mechanisms that facilitate the uptake of microplastics is essential for the evaluation of possible implications for marine organisms and food webs. Gastropods produce mucus for locomotion. Gastropod pedal mucus naturally retains formerly suspended micro-organisms, such as bacteria, microalgae, and seaweed spores. The retained organisms are consumed by gastropods that forage on pedal mucus. Here, we investigated the potential of gastropod pedal mucus to retain suspended microplastic particles and make them available for ingestion by periwinkles that forage on the contaminated mucus. In laboratory experiments, mucus of the periwinkles Littorina littorea and Littorina obtusata efficiently retained microplastics. Retention of microplastics varied between mucus from conspecifics of different size but not between mucus from either species. The density of microplastics in mucus trails increased concomitantly with the experimental particle concentration but was independent of incubation time. Aging of mucus and, particularly, desiccation affected the retention of microplastics. Periwinkles ingested microplastics when foraging on the contaminated mucus. Our results reveal a functional link between biogenic accumulation of microplastics and their trophic transfer by marine benthic herbivores into marine food webs. Graphical abstract: Image 1 Highlights: Gastropod pedal mucus promotes uptake of microplastics by benthic consumers. Pedal mucus from different periwinkles retains suspended microplastics. Retention of microplastics varies with characteristics of the mucus. Periwinkles readily ingest microplastics when foraging on contaminated pedal mucus. Substantial amounts of ingested microplastics are released with fecal material.